An investigation of the association of thromboembolic disease in patients admitted with COVID-19 in Gloucestershire Royal Hospital. (2021) - Alaee, Seema; Iftikhar, Hina; Kaminski, Rachel; Sharp, Charles; Bennett, Jessica
No abstract available